Kehendak Negara dalam Perjanjian Internasional - Hetharie, Brandon Tanner; Wattimena, Josina Agusthina Yvonne; Daties, Dyah Ridhul Airin (Uti Possidetis: Journal of International Law, 2025)
Background: International cooperation through treaties establishes legally binding obligations for states that have expressed their consent to be bound under international law. In practice, however, the exercise of state will as an expression of sovereignty often comes into tension with these binding legal norms. In this context, what is often perceived as a disregard for treaty compliance does not indicate the absence of binding legal force, but rather reflects juridical tensions between treaty obligations and the exercise of state will.This study examines how state will operates within the framework of treaty compliance and influences the binding legal force of international treaties. Methodology: This research uses a normative juridical method with statutory, case-based, and conceptual approaches. Data were collected from primary, secondary, and tertiary legal materials through literature review and analyzed qualitatively and descriptively. Objectives: The study aims to analyze the binding legal force of international treaties and to examine the juridical tensions that arise when state will conflicts with treaty compliance and implementation. Findings: The binding force of international treaties constitutes a complex legal construction that cannot be fully understood through a purely legalistic approach. A multidimensional analysis incorporating juridical, philosophical, sociological, and theoretical perspectives demonstrates that state compliance with international treaties is shaped not only by legal obligation, but also by domestic political dynamics and strategic national interests. In practice, these factors generate an asymmetry of state will in treaty compliance, whereby disparities in political power and legal capacity allow stronger states greater flexibility than developing states.Originality/Novelty: By situating state will within the juridical framework of treaty compliance, this study offers a contemporary legal analysis of how binding treaty obligations interact with political realities in modern international law.